An ecofriendly graphene-based nanofluid for heat transfer applications - Mehrali, M.; Sadeghinezhad, E.; Akhiani, A.R.; Latibari, S.T.; Talebian, S.; Dolatshahi-Pirouz, A.; Metselaar, H.S.C.; Mehrali, M. (Elsevier, 2016)
Herein, a new ecofriendly approach to generate a graphene-based nanofluid was established. Specifically, a novel mode of graphene oxide reduction through functionalization with polyphenol extracted from red wine was introduced. Comprehensive characterization methods were employed to confirm and understand the reduction process of graphene oxide in the red wine polyphenol solution. It was noted, that the deoxygenation level of the reduced graphene oxide is comparable with the levels obtained by conventional and non-ecofriendly methods. The physical and thermal properties of the generated nanofluid including chemical stability, viscosity, wettability, electrical conductivity and thermal conductivity were investigated in a comprehensive manner. A significant thermal conductivity enhancement amounting to 45.1% was obtained for a volume fraction of 4%. In addition, the convective heat transfer coefficient of the nanofluid in a laminar flow regime with uniform wall heat flux was investigated to estimate its cooling capabilities. These results, firmly confirm that the generated graphene-based nanofluid is a formidable transporter of heat and yet ecofriendly. Therefore, it's anticipate that the generated nanofluid will open a new avenue in the pursuit of ecofriendly thermal conductors for heat transfer applications.